Aplikasi Penentuan Rute Distribusi LPG 3 Kg - Difana Meilani; Arefa Iswara (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2018)
PT IB. Sumberdaya Development is one of LPG agent partners of PT Pertamina. This company is assigned to distribute 3 kg LPG. The LPG shipment is carried out from Monday to Saturday. The shipment goes to 66 depots using agent vehicle which are registered in PT Pertamina. From the preliminary study, there were problems which related to the long-distance shipment, and the limitation of transportation and capacity. In this research, the shipment routes of 3 kg LPG in PT IB is determined. Sumberdaya Development problems consist of the distance of the travel, the time of travel, and optimal transportation cost. Based on Clarke and Wright Savings Matrix algorithm, by considering the vehicle capacity, the distance can be minimized. The point of this algorithm is calculating the saving by measuring the available reduction of distance and time. It is done by linking the existing depots and making a route which is based on the largest saving value of the distance from the agent to the destination depot. Each route is optimized by WIN QSB software by using Branch and Bound method. A program to facilitate the determination of shipment routes by using PHP programming language is designed. The proposed route for the 3kg LPG shipment is 762.35km with 33.58% saving, and the proposed time is 2929 minutes with 15.27% saving. The shipment schedule is designed from Monday to Saturday day to Saturday with each of 7 routes. This is better than the actual route used by the company.